Hukum Perlindungan Konsumen Terhadap Ketidaksesuaian Label Harga Perspektif UUPK No. 8 Tahun 1999 - Alimatus Sa'diyah; Ayu Sadewi Rahmawati; Dian Eka Lestari; Diva Satria Putri Dinasti Wibisono; Gita Egis Triyani; Ijazatul Khoiriyah; Medina Aulyan Sahara; Murni Kasiyati (Academica: Journal of Multidisciplinary Studies, 2023)
The price tag is something for the price of an item that has been printed in front of the item. Price tags function as a tool to make it easier for consumers to see the price of an item to be purchased by being able to see directly the price of the item posted on the shelf, this is useful so that consumers do not have to ask the shopkeeper again if they want to buy an item they want. This study aims to use price tags that do not match the real price in the UUPK review No. 8 of 1999. The research method uses literature study, namely trying to examine various literature such as laws and regulations, research results and other legal references. With the existence of a price tag, it will be easier for people to meet their needs. However, behind these advantages there are also disadvantages, one of which is the difference in the price listed on the shelf with the price being paid. This is detrimental to consumers because consumers do not obtain certainty of the real price of the goods they want. Because it is necessary to have a regulation to protect consumer rights where the regulations governing consumer protection have been listed in Law No. 8 of 1999. Business actors must provide definite and clear information to consumers. Consumers need to receive protection and legal certainty regarding consumer rights regulated in consumer protection laws.